The Effect of E-Sports Games on Stress Hormones and Biochemical Parameters of Athletes - Ayhan, Savaş (Pakistan Journal of Medical & Health Sciences, 2022)
Background: It is suggested that there is a relationship between e-sports games on stress hormones and biochemical parameters of athletes. Aim: The most distinguishing feature of digital games is competition, stress, and physiological changes in the organism. It is a significant event that includes these features in e-sports, which is becoming increasingly popular in the digital world. The physiological and psychological effects of e-sports, which are performed in a competitive environment, on the organism during competitions are unknown. The purpose of this study was to determine the effects of players competing in e-sports competitions on some hormonal and biochemical parameters formed in the organism during the tournaments. Methods: In the research group, there were 20 volunteer male e-sports players competing in e-sports competitions. Samples were taken from the players in the research 30 minutes before and after an e-sports match. In the samples taken; Cortisol, ACTH, testosterone, glucose, insulin, urea, creatinine, bilirubin direct and total bilirubin levels were determined. Results: As a result of the study, it was revealed that e-sports players’ cortisol, ACTH, and testosterone levels increased significantly. It was determined that there was a statistical difference in the stress hormones pre-post test values of the research group (p<0.05). While it was determined that there was a significant difference in the pre-post test values of the participants’ glucose, insulin, urea, creatinine and bilirubin total levels (p<0.05), there was no statistically significant difference in the direct level of bilirubin (p>0.05). Conclusion: As a consequence, stress, anxiety, and physiological effects experienced during e-sports competition have been shown to significantly affect stress hormones and some biochemical parameters. In light of these observations, we believe that it would be beneficial to consider these parameters in order to enhance the performance of e-sports players.